Efektifitas Model Contextual Teaching And Learning (CTL) Berbasis Etnosains Terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPA - Anjani, Lela Ayu; Ramadhani, Erfan; Fahrudin, Ali (ANTHOR: Education and Learning Journal, 2023)
This study aims to determine the effectiveness of the ethnoscience-based contextual teaching andlearning (CTL) model on students' motivation in learning science. SDN 5 Talang Kelapa as manyas 350 people. The population is continued by being selected using a purposive samplingtechnique. The research method used in this study was quasi-experimental with the design usedwas Nonequivalent Control Group Design and the population in this study were students. Datacollection techniques used are questionnaires and documentation as secondary data. Based on theresults of the research and discussion, it can be concluded that the ethnoscience-based CTL(Contextual Teaching and Learning) learning model is effective for students' learning motivation in learning science. This can be proven by the value of Sig. = 0.015 less than alpha (α) = 0.05; with a t-count value of 2.500 and a t-table value of 1.672. It turns out that t-count > t-table or2.500 > 1.672, then reject then Ho is rejected and Ha is accepted.